Putting the WHO Global Patient Safety Action Plan into Practice: Establishing the Austrian Patient Council as a Best Practice Example of Patient Involvement - Anna Teufel MA; Elisabeth Klager MSc; Hannah Hausegger Bsc, BA; Christiane Grill PhD; Benjamin Schuster BSc; Maria Kletecka-Pulker PhD; Eva Schaden MD (Journal of Patient Experience)
Including the patient perspective in health research is not merely beneficial but essential. The establishment of the Austrian Patient Council serves as a practical example of how this goal can be effectively realized. This comprehensive mixed methods study offers valuable insights into the preparatory, foundational, and evaluative steps involved in setting up such a council. By analyzing online surveys conducted at two different points in time and conducting qualitative interviews, the study highlights the critical factors contributing to the council's success. These include selecting research topics of genuine interest to council members; establishing a robust project and administrative structure; ensuring the council is of an appropriate size; and that its membership is diverse and heterogeneous. The study also underscores the importance of implementing measures to facilitate and support active participation, and the need for continuous feedback and flexibility. Overall, the findings demonstrate that patient involvement in health research is feasible and provides a roadmap for meaningful engagement.